Two New Families and a New Species of Myxosporeans (Myxozoa, Myxosporea) from the Mediterranean and Black Sea Fishes - Yurakhno, V.M. (Вестник зоологии, 2011)
Descriptions of two new families – Polysporoplasmidae fam. n. (Syn. Sphaerosporidae Davis, 1917 in Sitja-Bobadilla, Alvarez-Pellitero, 1995) and Gadimyxidae fam. n. (syn. Parvicapsulidae Schulman, 1953 in Køie et al., 2007), and one new species of myxosporeans – Gadimyxa ovale sp. n. – parasites of fishes of the Mediterranean and the Black Seas are presented. Species of the genus Gadimyxa is found for the first time in the Black Sea. Описаны два новых семейства – Polysporoplasmidae fam. n. (син. Sphaerosporidae Davis, 1917 по Sitja-Bobadilla, Alvarez-Pellitero, 1995) и Gadimyxidae fam. n. (син. Parvicapsulidae Schulman, 1953 по Kшie et al., 2007), а также нового вида миксоспоридий – Gadimyxa ovale sp. n. – паразитов рыб Средиземного и Чёрного морей. Вид из рода Gadimyxa впервые заре-гистрирован в Чёрном море.